Human resource analysis and management using mobile edge computing. (14th July 2022) - Wang, Changlin
The purpose is to process large data, classify unclear information in the human resource management system, and improve the human resource management efficiency for enterprises. Here, a new system is proposed for human resource analysis and management based on Mobile Edge Computing (MEC) technology. First, the MEC technology is analysed. Then, the MEC technology is integrated into the human resource management system through network protocol according to the distributed computing function of MEC technology and human resources management requirements. Subsequently, the B/S and C/S data models are combined. Finally, the new human resource analysis and management model is proposed through the combination of B/S and C/S data models based on MEC. The proposed system can manage human resources and business operations locally to save transportation costs and increase system calculation speed through a series of analyses and research, and thus improving system performance.